Dynamics of International Standard Schools in Indonesia: Between Improving Quality and Access Inequality - Fiksi Juita; Fajri Ismail; Indah Wigati; Yuniar (Edumaspul: Jurnal Pendidikan, 2026)
This article critically examines the policy dynamics and implementation of International Standard Schools (SBI) and their subsequent transformation into Partnership Education Units (SPK) in Indonesia, with a specific focus on the tension between educational quality enhancement and access inequality. Employing a qualitative research design, this study utilizes comprehensive policy document analysis alongside a systematic literature review of peer-reviewed academic publications from 2020 to 2026. The findings reveal that integrating international curricula, advancing pedagogical teacher competencies, and adopting English as a medium of instruction significantly improve instructional quality and students’ global readiness. Conversely, the implementation faces substantial criticism due to prohibitively high operational costs, urban-centric institutional distribution, and selective admission mechanisms, which collectively risk exacerbating socioeconomic stratification within the national education system. The analysis indicates that the regulatory transition from SBI to SPK reflects a deliberate governmental recalibration aimed at balancing global educational benchmarks with constitutional mandates for equity. This study concludes that optimizing international standard education necessitates inclusive policy interventions, including means-tested financial assistance, targeted infrastructure and teacher development in underserved regions, and rigorous financial transparency mechanisms. Ultimately, implementing these strategic measures can position international standards as effective catalysts for a more inclusive, high-quality, and sustainable national education transformation.